Empathic love therapy for adolescents living with HIV in Surabaya, Indonesia - Erika Martining Wardani; Riezky Faisal Nugroho; Siti Nurjanah; Syiddatul Budury; Iis Noventi (HIV & AIDS Review. International Journal of HIV-Related Problems)
Introduction Adolescents with human immunodeficiency virus (HIV)/acquired immune deficiency syndrome (AIDS) do not only experience physical pain. They are also vulnerable to psychological stress. One of the emotional problems impacting adolescents is depression, as taking life-long medications makes teens depressed. One of non-pharmacological therapies that can be applied is empathic love therapy (ELT). This study was to determine the effectiveness of ELT for adolescents living with HIV in Surabaya, Indonesia.